Heart Failure in post MI patients with persistent IRA occlusion: Prevalence, Risk Factors, and the Long-term Effect of PCI in the Occluded Artery Trial (OAT) - Jhaveri, Rahul R. (2012)
BACKGROUND: The incidence and predictors of heart failure (HF) post myocardial infarction (MI) with modern post-MI treatment have not been well characterized. METHODS AND RESULTS: 2201 stable patients with persistent infarct related artery occlusion > 24 hours after MI with left ventricular ejection fraction <50% and/or proximal coronary artery occlusion were randomized to percutaneous intervention plus optimal medical therapy (PCI) or optimal medical therapy (MED) alone. Centrally adjudicated HF hospitalizations for NYHA III/IV HF and mortality were determined in patients with and without baseline HF, defined as a history of HF, Killip Class > I at index MI, rales, S3 gallop, NYHA II at randomization, or NYHA > I prior to index MI. Long-term follow-up data were used to determine 7-year life-table estimated event rates and hazard ratios. There were 150 adjudicated HF hospitalizations during a mean follow-up of 6 years with no difference between the randomized groups (7.4% PCI vs. 7.5% MED, p=0.97). Adjudicated HF hospitalization was associated with subsequent death (44.0% vs. 13.1%, HR 3.31, 99% CI 2.21–4.92, p<0.001). Baseline HF (present in 32% of patients) increased the risk of adjudicated HF hospitalization (13.6% vs. 4.7%, HR 3.43, 99% CI 2.23–5.26, p<0.001) and death (24.7% vs. 10.8%, HR 2.31, 99% CI 1.71–3.10, p<0.001). CONCLUSIONS: In the overall OAT population, adjudicated HF hospitalizations occurred in 7.5% of subjects and were associated with increased risk of subsequent death. Baseline or prior HF was common in the OAT population and was associated with increased risk of hospitalization and death.